VERBA PERBUATAN DALAM BAHASA INDONESIA - Nana Novita Rianasari; Mukhlish Mukhlish (CARAKA, 2018)
The aims of this research are (1) to desceibe the form of action verb in Indonesian language, (2) determine the affixes maker of action verb in Indonesian language, (3)  describe the semantic valence level of action verb in Indonesian language, and (4) describe the semantic role marker valence level of action verb in Indonesian language. This research is descriptive qualitative research. The data of this research covers sentences which have action verb on its. The data collection was taken from (1) newspaper of Suara Merdeka (Maret 2018), (2) Kumpulan Cerpen Agama Apa yang Pantas Bagi Pohon Pohon (2016), (3) novel Dilan (2015), and (4) the book of Sejarah Indonesia Kelas XI (2017). The method used in this reasearch was observe attentively with taking note technique. The data analysis method used in this research was distribute evenly method with direct divide-element technique, reserve side technique, expansion technique, form-changed technique, and read markup technique. This research describe in informal method. The result of this research as follows  (1) the form of the action verb is infinitive verb and the decsend of affixes, (2) the affixes of action verb in Indonesian language are prefixes : meng-, ber-, and ter-. Confix ber-an and the combination of affixes ber- / –an; meng- / –kan; and meng- / -i, (3) the semantic valence level of action verb in Indonesian language are (a) Agentive-Verb-Object- (Location), (b) Agentive-Verb-Object-Benefactive, (c) Agentive-Verb-Benefactive–Object, (d) Experience-Verb-Object, (e) Experience-Verb-Object-(Time), (f) Experience-Verb-Object-(Location), (g) Agentive-Verb-Location, (h) Agentive-Verb-Location-(Time), (i) Instrument-Verb-Location, and (j) Instrument-Verb-Object. The semantic role marker valence level of action verb in Indonesian language  are (a) preposition : oleh as the role of Agentive, (b) preposition : untuk and kepada as the role of Benefactive; (c) preposition : di, ke, and dari as  the role of Location; (d) preposition pada and nomina which indicates time as the role of Time; (e) preposition: dengan as the role of Insrument; and (f) preposition : dari as the role of Source.